MED1 Deficiency in Macrophages Accelerates Intimal Hyperplasia via ROS Generation and Inflammation. (22nd November 2021) - Zhang, Yali; Fu, Yu; Zhang, Chenyang; Jia, Linying; Yao, Nuo; Lin, Yuhao; Dong, Yue; Fatima, Nazira; Alam, Naqash; Wang, Rong; Wang, Weirong; Bai, Liang; et al.
Abstract : Mediator complex subunit 1 (MED1) is a component of the mediator complex and functions as a coactivator involved in the regulated transcription of nearly all RNA polymerase II-dependent genes. Previously, we showed that MED1 in macrophages has a protective effect on atherosclerosis; however, the effect of MED1 on intimal hyperplasia and mechanisms regulating proinflammatory cytokine production after macrophage MED1 deletion are still unknown. In this study, we report that MED1 macrophage-specific knockout (MED1 Δ Mac ) mice showed aggravated neointimal hyperplasia, vascular smooth muscle cells (VSMCs), and macrophage accumulation in injured arteries. Moreover, MED1 Δ Mac mice showed increased proinflammatory cytokine production after an injury to the artery. After lipopolysaccharide (LPS) treatment, MED1 Δ Mac macrophages showed increased generation of reactive oxygen species (ROS) and reduced expression of peroxisome proliferative activated receptor gamma coactivator-1 α (PGC1 α ) and antioxidant enzymes, including catalase and glutathione reductase. The overexpression of PGC1 α attenuated the effects of MED1 deficiency in macrophages. In vitro, conditioned media from MED1 Δ Mac macrophages induced more proliferation and migration of VSMCs. To explore the potential mechanisms by which MED1 affects inflammation, macrophages were treated with BAY11-7082 before LPS treatment, and the results showed that MED1 Δ Mac macrophages exhibited increased expression of phosphorylated-p65 and phosphorylated signal transducer and activator of transcription 1 (p-STAT1) compared with the control macrophages, suggesting the enhanced activation of NF- κ B and STAT1. In summary, these data showed that MED1 deficiency enhanced inflammation and the proliferation and migration of VSMCs in injured vascular tissue, which may result from the activation of NF- κ B and STAT1 due to the accumulation of ROS.